Instructional design for the development of digital educational contents for smartphones - Claudia Domínguez Pérez; Javier Organista Sandoval; Maricela López Ornelas (Universidad de Guadalajara, 2018)
This study describes the development of digital educational contents through an instructional design that incorporated audiovisual elements to be consulted by smartphones. The methodology was based on the Research and Development approach. The first stage consisted of the development of digital educational content through the Instructional Design of Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, while the second part explored whether this type of development can function as a pedagogical tool for support for a formal course. The results presented are derived from the piloting carried out with 17 graduate students who were studying the subject of Statistics. Some students expressed that the use of digital educational content is pleasant and novel; however, there was confusion in a statistical procedure. It concludes on the moderate use of animations, the reinforcement of the pedagogical aspects of this type of developments and some contextual considerations for the consultation. This study offers recommendations for optimizing audiovisual resources to provide pedagogical support in mobility contexts.